PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 005 SUNGAI PINANG KECAMATAN KUBU - Uziana '; Damanhuri Daud Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack:The background of this research is the process of learning and teaching fifth grade elementary school of 005 Sungai Pinang Kubu district in science subjects which are still dominated by the teacher so that students become passive, as well as materials provided by the teacher and the learning outcomes are not satisfactory with an average value below KKM. This study aims to improve science learning outcomes fifth grade students of SDN 005 Sungai Pinang Kubu district of Rokan Hilir. This study was conducted as two cycles by the number of students 20. Data were collected through observation using the observation sheet to the data model of cooperative Numbered Head Together (NHT) through the UAS I and UAS II for learning outcomes data. The percentage of all teachers in the first cycle was 60.71% (categories: enough) while in the second cycle was 92.85%. (categories: very good), while the percentage of student activity in the first cycle was 64.28% (categories: good) while the second cycle was 96.42%. (categories: very good). Average student learning outcomes has increased. Average student learning outcomes in basic score is 61.05, 66.25 in the first cycle and the second cycle 78.00. From the analysis of student learning outcomes scores increased from the base to the first cycle with a large increase of 8.51. While in the first cycle to the second cycle there was an increase of 17.7. From the research and discussion as it has been described above that the use of cooperative learning model NHT correctly then the activity and student learning outcomes be improved and better. This information proved that the hypothesis which says With Application of Cooperative Learning Model Type NHT can improve science learning outcomes Elementary School fifth grade students 005 Sungai Pinang Kubu district Rokan Hilir "acceptable".   Keywords: Cooperative LearningModelTypeNumbered Head Together(NHT), Learning Outcomes